Developmental and tissue-specific regulation of mouse telomerase and telomere length. - Prowse, K R (1995)
Telomere shortening and telomerase activation in human somatic cells have been implicated in cell immortalization and cellular senescence. To further study the role of telomerase in immortalization, we assayed telomere length and telomerase activity in primary mouse fibroblasts, in spontaneously immortalized cell clones, and in mouse tissues. In the primary cell cultures, telomere length decreased with increased cell doublings and telomerase activity was not detected. In contrast, in spontaneously immortalized clones, telomeres were maintained at a stable length and telomerase activity was present. To determine if telomere shortening occurs in vivo, we assayed for telomerase and telomere length in tissues from mice of different ages. Telomere length was similar among different tissues within a newborn mouse, whereas telomere length differed between tissues in an adult mouse. These findings suggest that there is tissue-specific regulation of mouse telomerase during development and aging in vivo. In contrast to human tissues, most mouse tissues had active telomerase. The presence of telomerase in these tissues may reflect the ease of immortalization of primary mouse cells relative to human cells in culture.